Kulturní dějiny? Kulturní dějiny! - Milena Lenderová (Theatrum Historiae)
The study focuses on the research into the place of everyday life in the context of cultural history, summarizing the notion and definition of culture, development of cultural history from the 18th century up to the discussion of European historiography that began in the 60s' of the past century. Semiotic (symbolic) determination of culture based on social (cultural) anthropology is a methodology background of the everyday life history. This way of cultural history determination is not a method, but rather a more general category, a concept determined by its subject. Therefore cultural history may represent a theory providing the conditions for the determination of particular methods and particular topics on which the methods will be applied. In the research into the everyday life history, instead of structures and a "great" history, a new aspect of the history is pursued that works with different methods, concentrating on the experience and social practice of an individual. Historians of everyday life history describe and analyze the history "from the bottom" and "from inside", perceiving it in a certain social and geographical framework as a sample of human acting and behaviour and as an answer of given society to its environment, representing its life style. The variety of questions to be asked by the everyday life history leads to the understanding of a "ground level" of our civilization.